2019
DOI: 10.3389/fimmu.2019.00691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance and Immunosuppressive Pattern of Circulating and Infiltrating Subsets of Myeloid-Derived Suppressor Cells (MDSCs) in Epithelial Ovarian Cancer

Abstract: Myeloid-derived suppressor cells (MDSCs) expansion is a hallmark of cancer. Three major MDSC subsets defined as monocytic (M)-MDSCs, polymorphonuclear (PMN)-MDSCs and early stage (e)MDSCs can be revealed in human diseases. However, the clinical relevance and immunosupressive pattern of these cells in epithelial ovarian cancer (EOC) are unknown. Therefore, we performed a comprehensive analysis of each MDSC subset and immunosupressive factors in the peripheral blood (PB), peritoneal fluid (PF), and the tumor tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…Furthermore, IDO activity in peripheral blood was positively correlated with levels of circulating PD-L1 + CD8 + T-cells and CTLA-4 + Tregs, underlining the close interconnection between these immunosuppressive markers in the blood circulation (86,206). In early epithelial ovarian cancer, the level of IDO + mMDSCs and IDO + pmnMDSCs was significantly higher in the peripheral blood compared to the tumor microenvironment (207).…”
Section: Ido In the Peripheral Bloodmentioning
confidence: 87%
“…Furthermore, IDO activity in peripheral blood was positively correlated with levels of circulating PD-L1 + CD8 + T-cells and CTLA-4 + Tregs, underlining the close interconnection between these immunosuppressive markers in the blood circulation (86,206). In early epithelial ovarian cancer, the level of IDO + mMDSCs and IDO + pmnMDSCs was significantly higher in the peripheral blood compared to the tumor microenvironment (207).…”
Section: Ido In the Peripheral Bloodmentioning
confidence: 87%
“…Our results are in line with Cannioto et al but not with Lutgendorf et al . 21 22 Wu et al and Okla et al had already evaluated the presence of monocytic myeloid-derived suppressor cells in ovarian cancer, but only compared healthy controls with malignant cases 23 24. They concluded that cells were increased in patients with malignant tumors and that their presence correlated negatively with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These cells play an essential role in the maintenance of self-tolerance, but may also impede anti-tumor cell-mediated immune responses and promote cancer progression [90]. Although some disagreement is evident [107], several earlier studies have reported that MDSCs induce differentiation and/or proliferation of Foxp3+ Tregs in tumor-bearing mice [89,91,92] via mechanisms which involve the production of the immunosuppressive cytokines, IL-10 and TGFß1 [93,108]. In addition, others have reported that the monocytic subset of MDSCs has the ability to recruit Tregs to the tumor site in a CCR5-dependent manner, indicating that these cells may be most prominent with respect to the attraction of Tregs to the TME [94].…”
Section: Differentiation and Expansion Of Tregsmentioning
confidence: 99%